DIFFERENCES IN HEMATOCRIT LEVELS AND PLATELET COUNTS ON THE 4th To 6th DAY OF FEVER IN DENGUE HEMORRHAGIC FEVER PATIENTS - Ni Luh Hepy Karniawan; Moh.Fairuz Abadi; A.A.Ayu Eka Cahyani (PT. Jurnal Center Indonesia Publisher, 2025)
Dengue Hemorrhagic Fever (DHF) is an endemic disease in Indonesia caused by the dengue virus and transmitted through the bites of Aedes aegypti and Aedes albopictus mosquitoes. The risk of serious complications primarily arises during the critical phase, typically between the 4th and 6th days of fever, during which plasma leakage may occur, leading to shock and severe bleeding. Hematocrit levels and platelet counts are important parameters in the diagnosis and monitoring of DHF patients. This study aimed to determine the differences in hematocrit levels and platelet counts during days 4 to 6 of fever in DHF patients at Prima Medika Hospital Denpasar, in February 2025. This research employed a descriptive quantitative design with purposive sampling, involving 35 patients who met the inclusion criteria. The results showed a decrease in hematocrit levels with averages of 42.8%, 42%, and 41.2%, and platelet counts with averages of 87 x 10³/µL, 59 x 10³/µL, and 47 x 10³/µL from day 4 to day 6 of fever. Data were analyzed using the Shapiro-Wilk normality test, the Friedman non-parametric test for hematocrit levels, and the Repeated Measures ANOVA parametric test for platelet counts. Statistical analysis showed a p-value of 0.002 for hematocrit levels and 0.000 for platelet counts. The conclusion of this study is that there are significant differences in hematocrit levels and platelet counts between days 4 to 6 of fever in DHF patients.